A model of personality change after traumatic brain injury and the development of the Brain Injury Personality Scales. Issue 11 (26th January 2007) - Obonsawin, M C; Jefferis, S; Lowe, R; Crawford, J R; Fernandes, J; Holland, L; Woldt, K; Worthington, E; Bowie, G
Abstract : Objective: The aims of this study were to develop models of personality change after traumatic brain injury (TBI) based on information provided by the TBI survivor and a significant other (SO), and to compare the models generated from the two different sources of information. Methods: Individuals with and without TBI and an SO were interviewed separately about their current personality. The SOs were also interviewed about the personality of the TBI survivor before the injury. A subset of TBI survivors and their SOs were interviewed twice to assess test–retest reliability. Items which were not associated with personality change after TBI, which could not be measured reliably or which did not contribute to the model, were excluded. Results: Of the 123 original items, 29 items from the interview with the survivor and 31 items from the interview with the SO were retained to form the Brain Injury Personality Scales. Separate factor analyses of ratings from each interview (survivor and SO) resulted in seven first order factors. The second order factor analyses for each interview resulted in four factors. Concordance between the information obtained from the two interviews was low. Conclusions: The information obtained from the interviews with the TBI survivors and the SOs produced two models with a similar structure: three superordinate factors of personality items (affective regulation, behavioural regulation and engagement) and one superordinate factor of items relevant to mental state (restlessness and range of thought). Despite the similarity in structure, the content of the information obtained from the two interviews was different.